The Use of Antiepileptic Drugs in Paediatric Neurosurgical Conditions - Themistocleous, Marios S.; Giakoumettis, Dimitrios; Margetis, Konstantinos; Alexiou, George A.; Stranjalis, George (Current Pharmaceutical Design, 2017)
Background: Epileptic seizures are a relatively common problem in pediatric neurosurgery that can have physical, mental and/or behavioral implications. Pediatric neurosurgery is involved in the treatment of secondary epilepsy, which is mainly associated with brain tumors, traumatic brain injury and intracranial vascular malformations. Objective: The aim of this article is to review the current literature for commonly used antiepileptic drugs in pediatric neurosurgery and offer an updated view on epilepsy treatment with antiepileptic drugs in the most commonly encountered neurosurgical entities in the pediatric population. Methods and Materials: Current literature has been reviewed for epilepsy, antiepileptic drugs and common neurosurgical conditions in children that cause seizures and/or epilepsy. Epidemiological features, epileptogenesis and treatment have been thoroughly examined. Conclusion: The most common neurosurgical conditions that cause seizures and/or epilepsy in the pediatric population are brain tumors and traumatic brain injury. Newer antiepileptic drugs are powerful instruments in the management of epilepsy and they improve the quality of life of patients as well as decrease the epilepsy associated morbidity.
Keywords: neurosurgery